Aspirin-Loaded Polymeric Films for Drug Delivery Systems: Comparison between Soaking and Supercritical CO2 Impregnation - Isabela Trindade Coutinho (Pharmaceutics, 2021)
Polymeric implants loaded with drugs can overcome the disadvantages of oral or injection drug administration and deliver the drug locally. Several methods can load drugs into polymers. Herein, soaking and supercritical CO2 (scCO2) impregnation methods were employed to load aspirin into poly(l-lactic acid) (PLLA) and linear low-density polyethylene (LLDPE). Higher drug loadings (DL) were achieved with scCO2 impregnation compared to soaking and in a shorter time (3.4 ± 0.8 vs. 1.3 ± 0.4% for PLLA; and 0.4 ± 0.5 vs. 0.6 ± 0.5% for LLDPE), due to the higher swelling capacity of CO2. The higher affinity of aspirin explained the higher DL in PLLA than in LLDPE. Residual solvent was detected in LLDPE prepared by soaking, but within the FDA concentration limits. The solvents used in both methods acted as plasticizers and increased PLLA crystallinity. PLLA impregnated with aspirin exhibited faster hydrolysis in vitro due to the catalytic effect of aspirin. Finally, PLLA impregnated by soaking showed a burst release because of aspirin crystals on the PLLA surface, and released 100% of aspirin within 60 days, whereas the PLLA prepared with scCO2 released 60% after 74 days by diffusion and PLLA erosion. Hence, the scCO2 impregnation method is adequate for higher aspirin loadings and prolonged drug release.